Mystery road. Origin [videorecording (DVD)] - River, Dylan; McGregor, Steven (Screenwriter); Ayshford, Blake; Lee, Timothy (Screenwriter); Bedford, Kodie; Smith, Mark Coles, 1987-; Narkle, Tuuli; Henshall, Daniel, 1983-; Moore, Toby Leonard; Bisley, Steve, 1951-; Geransar, Salme; Ryan, Clarence; et al. (Acorn, 2022)
It's 1999, and freshly minted detective Jay Swan arrives in a dusty Outback town. Although he's the new copper on the beat, he grew up nearby, and his estranged family still lives here as does the woman who will change his life forever, Mary. Before Jay can even report for duty, he finds himself in the middle of an armed holdup, one of a series being perpetrated by a masked gang. The heists seem to be random: a cattle truck is stolen, a popular pub is held up, and a prominent family's home is burgled. Suspicion falls on a local company with petty crime connections, but the motive is murky. Meanwhile, legal aid lawyer Anousha stumbles onto the cold case of Mary's foster brother, murdered seven years earlier. As the investigations converge, Jay faces a tragic death, a burgeoning love, and the brutal reality of being a police officer straddling two worlds.